Existência e multiplicidade de soluções de problemas de contorno elípticos de quarta ordem via métodos topológicos - SILVA, Kaye Oliveira da (2012)
In this work, we employ topological methods in order to study existence and multiplicity of solutions, of nonlinear boundary value problems of the fourth order. More precisely, we make use of results on connected components of fixed points, as well as global bifurcation, to show existence and multiplicity of weak solutions of Partial Differential Equations, involving the Biharmonic operator under Navier boundary conditions. Proofs of the abstract results used, are presented in detail.